2019
DOI: 10.3389/fnagi.2019.00035
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Hypertension – Independent or Intertwined White Matter Impairing Factors? Insights From the Quantitative Diffusion Tensor Imaging

Abstract: Aging disrupts white matter integrity, and so does continuous elevated blood pressure that accompanies hypertension (HTN). Yet, our understanding of the interrelationship between these factors is still limited. The study aimed at evaluating patterns of changes in diffusion parameters (as assessed by quantitative diffusion fiber tracking – qDTI) following both aging, and hypertension, as well as the nature of their linkage. 146 participants took part in the study: the control group ( N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 52 publications
5
16
1
Order By: Relevance
“…Also, it should be noted that through our study we cannot determine causation. Although, repetitive concussions may explain our findings, comorbidities such as hypertension [31], obesity [32], or sleep apnea [33] should be considered as potential confounding factors as they may be responsible for imaging differences which are seen between individuals. In addition, we followed up the ExPro subgroup for only 2 years which is a relatively short period to track neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it should be noted that through our study we cannot determine causation. Although, repetitive concussions may explain our findings, comorbidities such as hypertension [31], obesity [32], or sleep apnea [33] should be considered as potential confounding factors as they may be responsible for imaging differences which are seen between individuals. In addition, we followed up the ExPro subgroup for only 2 years which is a relatively short period to track neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Higher arterial stiffness has been identified as a cause of higher blood pressure, which increases with aging, and has shown a negative association with WM integrity (Maillard et al., 2016). A recent study reported a significant hypertension by age interaction, suggesting accelerated WM loss (reflected by higher MD, AxD, RD) in middle-aged hypertensive adults, but only in the left hemisphere (Sabisz et al., 2019). Findings from a small number of longitudinal studies that have examined the relationship between WM integrity and hypertension over a period of 2 to 10 years have, however, been inconsistent.…”
Section: Modifiable Factors and Wm Microstructurementioning
confidence: 99%
“…Hypertension, or high blood pressure, in middle-aged and older adults is related to DTI metrics that reflect compromised WM integrity, particularly lower FA and higher MD values (Allen et al., 2016, Bender and Raz, 2015, de Groot et al., 2015, Gons et al., 2012, Hannawi et al., 2018, Maillard et al., 2012, Mcevoy et al., 2015, Power et al., 2017, Salat et al., 2012, Suzuki et al., 2017) (but see the study by Bender et al., 2016, de Groot et al., 2016, Sabisz et al., 2019). Interestingly, the associations between blood pressure and FA and MD are already detectable in preclinical stages (Maillard et al., 2012, Salat et al., 2012) (but see the study by Suzuki et al., 2017), and remain significant after controlling for age and WM lesions (Power et al., 2017, Salat et al., 2012).…”
Section: Modifiable Factors and Wm Microstructurementioning
confidence: 99%
“…Because of its strong connection to arterial stiffness and cerebral vascular disease, it is difficult to separate hypertension effects from the effects of other vascular impairments. Hypertension has been linked to declining brain health, including decreased gray matter volume, decreased cortical thickness, decreased fractional anisotropy, and increased white matter lesions (Gonzalez et al., 2015; Jennings & Zanstra, 2009; Sabisz et al., 2019). It has also been linked to declining cognition across a number of domains, including memory, executive function, and processing speed (Iadecola et al., 2016).…”
Section: How Does the Cerebrovasculature Change With Age?mentioning
confidence: 99%